Prospective longevity : a new vision of population aging - Sanderson, Warren C.; Scherbov, Sergei (Harvard University Press, 2019)
"The study of aging is not fundamentally about how old people are. It is about people's capabilities and their disabilities. In the field of population aging, measurements have generally been made with instruments devised many decades ago. Those measurements systems did not take the changing characteristics of older people into account. Using them 65-year-olds with a remaining life expectancy of 5 years could not be distinguished from 65-year-olds with a remaining life expectancy of 25 years. Although, in the past, those instruments did help us see better, it is now clear that there is a great deal that they did not allow us to see. Prospective Longevity provide a new view of who is old, how healthy people are in old age, the gender gap in survival at older ages, differences in patterns of survival across Russian regions and United States, the effects on the pace of population aging of medical breakthroughs that allow people to live much longer lives, and how an intergenerationally equitable pension age should change as life expectancy increases"--